The Adjustment of the Rotational Alignment of the Distal End of the Extramedullary Guide to the Anteroposterior Axis of the Proximal Tibia in Total Knee Arthroplasty - Mizu-uchi, Hideki; Kido, Hidehiko; Chikama, Tomonao; Kamo, Kenta; Kido, Satoshi; Nakashima, Yasuharu (The Journal of Knee Surgery, 2021)
The optimal placement within 3 degrees in coronal alignment was reportedly achieved in only 60 to 80% of patients when using an extramedullary alignment guide for the tibial side in total knee arthroplasty (TKA). This probably occurs because the extramedullary alignment guide is easily affected by the position of the ankle joint which is difficult to define by tibial torsion. Rotational direction of distal end of the extramedullary guide should be aligned to the anteroposterior (AP) axis of the proximal tibia to acquire optimal coronal alignment in the computer simulation studies; however, its efficacy has not been proven in a clinical setting. The distal end of the guide can be overly displaced from the ideal position when using a conventional guide system despite the alignment of the AP axis to the proximal tibia. This study investigated the effect of displacement of the distal end of extramedullary guide relative to the tibial coronal alignment while adjusting the rotational alignment of the distal end to the AP axis of the proximal tibia in TKA. A total of 50 TKAs performed in 50 varus osteoarthritic knees using an image-free navigation system were included in this study. The rotational alignment of the proximal side of the guide was adjusted to the AP axis of the proximal tibia. The position of the distal end of the guide was aligned to the center of the ankle joint as viewed from the proximal AP axis (ideal position) and as determined by the navigation system. The tibial intraoperative coronal alignments were recorded as the distal end was moved from the ideal position at 3-mm intervals. The intraoperative alignments were 0.5, 0.9, and 1.4 degrees in valgus alignment with 3-, 6-, and 9-mm medial displacements, respectively. The intraoperative alignments were 0.7, 1.2, and 1.7 degrees in varus alignment with 3-, 6-, and 9-mm lateral displacements, respectively. In conclusion, the acceptable tibial coronal alignment (within 2 degrees from the optimal alignment) can be achieved, although some displacement of the distal end from the ideal position can occur after the rotational alignment of the distal end of the guide is adjusted to the AP axis of the proximal tibia.
Keywords: total knee arthroplasty; tibial coronal alignment; extramedullary alignment guide; anteroposterior axis; computer navigation system